Development of functional cookies with Cerrado fruits and residues: sensory analysis, nutrients, and bioactive compounds - CAMPOS,Clélia de Moura Fé (2022)
Abstract In this study, we determined the nutritional and functional characteristics of cookies supplemented with chichá almond, gurguéia nut, and soursop residue using two developed cookie formulations and one standard formulation. Acceptance and purchase intention were evaluated. As the chichá almond 6 and gurguéia nut 2 formulations were sensorially viable, descriptive quantitative analysis, centesimal composition and caloric value, mineral levels, microbiological quality, bioactive compound levels, and antioxidant capacity were evaluated. In the hedonic scale test of the standard cookie, the chichá almond-6 and gurguéia nut-2 cookies obtained scores above 7 (“I liked it”) from 86.18%, 96.35%, and 93% of the evaluators, and 70.79%, 94.36%, and 83.2% of them said they would purchase the product, showing a statistically significant difference between formulations. The chichá almond 6 cookie presented higher ash, protein, lipid, copper, phosphorus, magnesium, potassium, selenium, and zinc levels, and lower carbohydrate levels and total energy values, as well as a higher total phenolic compound, total flavonoid, and condensed tannin levels. The gurguéia nut 2 cookie showed higher vitamin C and antioxidant activity. The use of residue and Cerrado fruit flour proved to be viable in cookie production, conveying sensorially desirable, nutritional, and functional characteristics.